2018
DOI: 10.1259/dmfr.20170147
|View full text |Cite
|
Sign up to set email alerts
|

Cluster signal-to-noise analysis for evaluation of the information content in an image

Abstract: Cluster signal-to-noise analysis can simulate the detection performance of observers and thus replace the observer performance test in the evaluation of image quality. Erroneous decision-making increased with increasing background noise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Additionally, our quantitative evaluation method employing the holes to simulate small mass changes could be applied to evaluate not only MCs, but also bone defects or caries in clinical situations. Weerawanich et al 17 developed a new image quality evaluation method that had a higher correlation with observer performance with several cut-off values; however, its relationship to diagnostic performance is still unclear. Although the number of cut-off values (threshold gray value or ΔG) in this method is limited, we confirmed that diagnostic performance was reflected in the number of extracted holes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our quantitative evaluation method employing the holes to simulate small mass changes could be applied to evaluate not only MCs, but also bone defects or caries in clinical situations. Weerawanich et al 17 developed a new image quality evaluation method that had a higher correlation with observer performance with several cut-off values; however, its relationship to diagnostic performance is still unclear. Although the number of cut-off values (threshold gray value or ΔG) in this method is limited, we confirmed that diagnostic performance was reflected in the number of extracted holes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our method is simpler than Weerawanich's method. 17 There are many comparative studies about diagnostic performance using ROC analysis with several kinds of objectives, while changing scanning conditions or systems. 15,[18][19][20][21][22] ROC analysis is affected by these factors but it eventually derives the result as "diagnostic accuracy".…”
Section: Discussionmentioning
confidence: 99%